A recent distemper virus outbreak in the growing canine populations of Galapagos Islands: a persistent threat for the endangered Galapagos Sea Lion - Vega-Mariño, Patricio; Olson, Jessie; Howitt, Ben; Criollo, Rita; Figueroa, Lissette; Orlando, Solon Alberto; Cruz, Marilyn; Garcia-Bereguiain, Miguel Angel (Frontiers in Veterinary Science, 2023)
Canine Distemper Virus (CDV) is a highly contagious virus that can cross mammal species barriers and has widespread impacts on both domestic and wildlife animal populations. This study describes a recent outbreak of CDV in Galapagos Islands in 2019. A total number of 125 dogs with clinical signs compatible with CDV were included in this study. Nasal swabs were taken and analysed by RT-qPCR for the detection of CDV, resulting in a positivity rate of 74,4% (IC95%, 66-81%). Among the CDV positive dogs, 82.2% presented respiratory signs, 48.8% neurological signs, and 28.9% gastrointestinal signs. CDV has been previously reported in the domestic canine population of the Galapagos Islands in 2001 and 2004. The current study shows how CDV is still a threat for the endemic and endangered Galapagos sea lion, despite recent policies for dog population control and CDV vaccination.